2017
DOI: 10.3389/fncir.2017.00035
|View full text |Cite
|
Sign up to set email alerts
|

Circuits Regulating Pleasure and Happiness in Bipolar Disorder

Abstract: According to our model, the motivation for appetitive-searching vs. distress-avoiding behaviors is regulated by two parallel cortico-striato-thalamo-cortical (CSTC) re-entry circuits that include the core and the shell parts of the nucleus accumbens, respectively. An entire series of basal ganglia, running from the caudate nucleus on one side to the centromedial amygdala on the other side, control the intensity of these reward-seeking and misery-fleeing behaviors by stimulating the activity of the (pre)frontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…24 Moreover, many findings in human and animal studies indicate an association between cholinergic hyperactivity and bipolar depression. 25,26 The same mechanism, which in theory might involve insufficient activity of inhibitory CHRM4, might also induce suicidality in patients with schizophrenia. Therefore, we believe that the findings of Scarr et al might be related to the specific deceased patient sample they studied.…”
Section: Discussionmentioning
confidence: 99%
“…24 Moreover, many findings in human and animal studies indicate an association between cholinergic hyperactivity and bipolar depression. 25,26 The same mechanism, which in theory might involve insufficient activity of inhibitory CHRM4, might also induce suicidality in patients with schizophrenia. Therefore, we believe that the findings of Scarr et al might be related to the specific deceased patient sample they studied.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical dysfunction in neuropsychiatric disorders is associated with mood disorders, depression and psychosis (Loonen et al, 2017; Shrestha et al, 2015; Sigurdsson et al, 2010). Genetic variants of Nrgn have been associated with cortical degeneration (Thong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Port et al found decreased levels of creatine and choline in the right caudate nucleus of bipolar patients compared to controls. Their finding is significant since malfunctioning of the caudate nucleus is involved in the pathogenesis of the bipolar disorder …”
Section: Creatine Administration In Conditions Of Brain Energy Shortagementioning
confidence: 99%
“…Their finding is significant since malfunctioning of the caudate nucleus is involved in the pathogenesis of the bipolar disorder. 123,124 It is interesting to note that in a study on the antidepressant effect of tri-iodothyronine, the depressed patients who responded to this treatment also showed increased cerebral phosphocreatine levels compared to the baseline measurement. This study showed also that higher baseline levels of cerebral phosphocreatine predicted the subsequent clinical response to tri-iodotironin 125 (83% sensitivity and 75% specificity).…”
Section: Depressed Mood Disordermentioning
confidence: 99%